2019
DOI: 10.1109/jsac.2018.2872372
|View full text |Cite
|
Sign up to set email alerts
|

Secure SWIPT for Directional Modulation-Aided AF Relaying Networks

Abstract: Secure wireless information and power transfer based on directional modulation is conceived for amplify-andforward (AF) relaying networks. Explicitly, we first formulate a secrecy rate maximization (SRM) problem, which can be decomposed into a twin-level optimization problem and solved by a one-dimensional (1D) search and semidefinite relaxation (SDR) technique. Then in order to reduce the search complexity, we formulate an optimization problem based on maximizing the signal-to-leakage-AN-noise-ratio (Max-SLAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Since radio frequency (RF) signals can simultaneously carry both energy and information [41], SWIPT enabled relay/receivers can glean energy from the received signal for their future signal transmissions, while simultaneously decoding the received information symbols [42]. In addition, they have been shown to significantly improve the overall transmission performance [39], [43]- [45]. for large blocklength scenarios.…”
Section: A Review Of the Existing Literaturementioning
confidence: 99%
“…Since radio frequency (RF) signals can simultaneously carry both energy and information [41], SWIPT enabled relay/receivers can glean energy from the received signal for their future signal transmissions, while simultaneously decoding the received information symbols [42]. In addition, they have been shown to significantly improve the overall transmission performance [39], [43]- [45]. for large blocklength scenarios.…”
Section: A Review Of the Existing Literaturementioning
confidence: 99%
“…Authors in [34] investigated the robust weighted sum secrecy rate maximization design, subject to multiple signal-to-interference-and-noise ratio and harvested energy constraints. A secrecy rate maximization (SRM) problem is formulated in [35], which can be decomposed into a twinlevel optimization problem and solved by a one-dimensional (1D) search and semi-definite relaxation (SDR) technique. It is observed that Time Split scheme outperforms the Power split scheme [36] in terms of achieving a higher covert rate when the transmit power at the source is relatively low.…”
Section: A Related Workmentioning
confidence: 99%
“…Furthermore, in [26,27], the concept of robust DM was extended to two new scenarios: multi-beaming broadcasting and MU-MIMO, respectively. The authors in [28,29] utilized relay-aided DM to enhance the physical layer security. In addition, the authors in [28,30,31] extended DM to secure precise wireless transmission (SPWT) scenario.…”
Section: Introductionmentioning
confidence: 99%